Vplivi evropske avantgarde na odnos med literaturo in glasbo v delih Jakoba Ježa - Vrhunc, Larisa (Muzikološki zbornik, 2014)
One of Jakob Jež's favourite instruments is the vocal; he has therefore dedicated much of his time to the selection of textual material and its incorporation into his music. Composers' attitude towards literature has been changing throughout history, with the post-war avant-garde period offering many innovative solutions, which is also reflected in the vocal and instrumental music by Jakob Jež.
Keywords: 2. polovica 20. st.; avantgarda; izbira besedila; Jež, Jakob, 1928-; vokalna glasba